Problematika Eksekusi Putusan Arbitrase Internasional: Studi Komparatif Antara Regulasi Nasional Dan Uncitral Model Law - Lintang Yudhantaka; Fitri Nur Amalia (PMIH Untag Semarang, 2026)
The Arbitration Law in Indonesia (Law No. 30 of 1999) contains provisions that largely concern domestic arbitration. Only a few articles regulate international arbitration, and even then, they mainly relate to international arbitral awards. However, the classification of international arbitral awards under Law No. 30 of 1999 differs from the regulation under international law, as provided in the UNCITRAL Model Law on International Commercial Arbitration 1985 with Amendments as Adopted in 2006 (UNCITRAL Model Law), thereby giving rise to different legal consequences. This article discusses the characteristics of international arbitral awards and the legal consequences of enforcing international arbitral awards from the perspective of national regulations, namely Law No. 30 of 1999, Supreme Court Regulation No. 3 of 2023, and Constitutional Court Decision No. 100/PUU-XXII/2024, as well as the UNCITRAL Model Law. Through legal research using statutory, conceptual, and comparative approaches, the study finds that the classification of international arbitral awards as regulated in several current national regulations still results in the expansion of court authority in handling cases containing foreign elements.